The Great American Dust Bowl - Brown, Don, 1949- (Boston : Houghton Mifflin Harcourt, 2013)
The causes and results of the Dust Bowl and how the lessons learned are still used today. Presented in comic book format.
Includes bibliographical references (pages 78).
Keywords: Dust Bowl Era, 1931-1939 -- Comic books, strips, etc; Depressions -- Comic books, strips, etc -- 1929 -- Great Plains; Dust storms -- Comic books, strips, etc -- History -- 20th century -- Great Plains; Droughts -- Comic books, strips, etc -- History -- 20th century -- Great Plains; Farm life -- Comic books, strips, etc -- History -- 20th century -- Great Plains; Farmers -- Comic books, strips, etc -- Social conditions -- 20th century -- Great Plains; Comic books, strips, etc; Graphic novels; Depressions -- Cartoons and comics. -- 1929; Dust storms -- Cartoons and comics. -- Great Plains; Droughts -- Cartoons and comics. -- Great Plains; Farm life -- Cartoons and comics. -- Great Plains; Dust Bowl Era, 1931-1939 -- Cartoons and comics; Cartoons and comics; Great Plains -- Comic books, strips, etc -- History -- 20th century; Great Plains -- Comic books, strips, etc -- Social conditions -- 20th century; Great Plains -- Cartoons and comics. -- History; Comic books, strips, etc; Graphic novels